(untitled) (Tempo e Argumento, 2022)
The paper analyses the voice of children in bearing witness to conflictive events in recent history. Following the Chilean social outburst starting on 18 October 2019, a letter-writing experience was conducted with 46 students between 11 and 14 years old in two primary schools in the city of Santiago de Chile. The main findings of the activity indicate that boys and girls express themselves as authorised voices to narrate the event that erupted in society, they express ethical evaluations of what happened by understanding facts through contingent and structural situations. Some students articulate the events of the present (social demands, human rights violations) with the legacy of the civil-military dictatorship (1973- 1990), pointing out similarities between the two events. These findings allow us to affirm that children are valuable voices to bear witness to the history of the present within the framework of a pedagogical device.